The funding of specialised paediatric palliative care in Switzerland: a conceptualisation and modified Delphi study on obstacles and priorities (Swiss Medical Weekly, 2023)
BACKGROUND: Effective funding models are key for implementing and sustaining critical care delivery programmes such as specialised paediatric palliative care (SPPC). In Switzerland, funding concerns have frequently been raised as primary barriers to providing SPPC in dedicated settings. However, systematic evidence on existing models of funding as well as primary challenges faced by stakeholders remains scarce.AIMS: The present study’s first aim was to investigate and conceptualise the funding of hospital-based consultative SPPC programmes in Switzerland. Its second aim was to identify obstacles to and priorities for funding these programmes sustainably.METHODS: A 4-step process, including a document analysis, was used to conceptualise the funding of hospital-based consultative SPPC programmes in Switzerland. In consultation with a purposefully selected panel of experts in the subject, a 3-round modified Delphi study was conducted to identify funding-relevant obstacles and priorities regarding SPPC.RESULTS: Current funding of hospital-based consultative specialised paediatric palliative care programmes is complex and fragmented, combining funding from public, private and charitable sources. Overall, 21 experts participated in the first round of the modified Delphi study, 19 in round two and 15 in round three. They identified 23 obstacles and 29 priorities. Consensus (>70%) was obtained for 12 obstacles and 22 priorities. The highest level of consensus (>90%) was achieved for three priorities: the development of financing solutions to ensure long-term funding of SPPC programmes; the provision of funding and support for integrated palliative care; and sufficient reimbursement of inpatient service costs in the context of high-deficit palliative care patients.CONCLUSION: Decision- and policy-makers hoping to further develop and expand SPPC in Switzerland should be aware that current funding models are highly complex and that SPPC funding is impeded by many obstacles. Considering the steadily rising prevalence of children with life-limiting conditions and the proven benefits of SPPC, improvements in funding models are urgently needed to ensure that the needs of this highly vulnerable population are adequately met.